Water Balance Analysis for Irrigation Sustainability in the Way Kelutum Irrigation Area - Restika Putri; Dyah Indriana Kusumastuti; Frida Yassar Maula (International Journal of Hydrological and Environmental for Sustainability, 2026)
The sustainability of irrigated agriculture in regions with pronounced seasonal rainfall variability depends on maintaining a balance between water availability and crop water demand. This study evaluates the irrigation water balance in the Way Kelutum Irrigation Area, Pringsewu Regency, Lampung, Indonesia, through a semi-monthly analysis integrating crop water requirements and dependable river discharge. Crop water demand was estimated using the Penman–Monteith method, while dependable discharge at an 80% reliability level was calculated using the F.J. Mock model based on rainfall, climatological data, and watershed characteristics. The results indicate that effective rainfall contributes substantially to meeting crop water requirements during the early rainy season, whereas irrigation supply becomes the primary source of water during the dry season. The dependable discharge of the Way Kelutum River varies between 0.10 and 1.40 m³/s throughout the year. Semi monthly water balance analysis shows that available water resources are sufficient to support two rice-growing seasons over an irrigated area of 42.04 ha, while water deficits occur for secondary crops during the peak dry period. By emphasising intra-seasonal water balance dynamics rather than annual-scale averages, this study provides practical insights for determining operational cropping patterns in small-to-medium irrigation schemes, particularly under conditions of limited dry-season water availability.